Penerapan Diversi pada Tahap Penyidikan terhadap Anak Pelaku Tindak Pidana di Wilayah Hukum Kepolisian Resor Badung - Juniati, Ni Putu Nanik; Karyoto, Karyoto (Jurnal Studi Pemerintahan dan Akuntabilitas, 2022)
Purpose: The purpose of this research is to analyze the role of investigators in the application of diversion against children in conflict with the law and to analyze and identify the factors that have caused the failure of the diversion attempt at the investigation level. Methodology: The research entitled Application of Diversity at the Investigation Stage of Children of Criminal Actors in the Badung District Police Legal Area, uses empirical juridical research methods by comparing legal theories and statutory regulations with facts in the field. Results: Diversion that aims to provide protection for children in conflict with the law, children who are victims of criminal acts, and society in general as a form of transfer of the settlement of cases of children from criminal justice processes to processes outside of criminal justice in order to realize restorative justice (restorative justice). The problem raised in this study is how the role of investigators in the application of diversion against children of criminal offenses, due to if the diversion attempt failed to be carried out at the investigation level as well as the factors that caused the failure of the diversion attempt at the investigation level. The location of the study took place in the Badung Police Department especially the general criminal detective unit for handling women and children.